Obtención de alimentos funcionales de Bactris gasipaes (pijuayo) - Aspajo Aspajo, Andrea Isabel (2018)
Currently, the peach palm is highly sought after for having a fruit with a special flavor. The pulp of the peach palm when cooked is the most nutritious food of the fruits of the Amazon, since it has vitamin A, antioxidants, Omega 3 and Omega 6 as essential fatty acids as such. Most of the works tell us about the great benefits that it gives due to its great nutritional value that it contains as provitamin-A, vitamins such as A and E, antioxidants and essential fatty acids that can prevent many diseases in the future for people. In the present work, the research works that exist with the fruit of Bactris gasipaes will be reported to obtain functional foods and the benefits that the fruit offers us and also some productions that occur with the fruit of Bactris gasipaes; Development of a tortilla-type snack based on pijuayo fruit (Bactris gasipaes kunth), flour from the by-products of Bactris gasipaes hbk and its use in baking, preparation of fortified cookies with flour from Phaseolus vulgaris l (castilla bean) and Bactris gasipaes hbk (pijuayo) for human consumption.